Some regularities of diamond phase formation at nonequilibrium transition process of C vapors with low Ті concentration into condensed state - Perekrestov, V.I.; Kosminskaya, Yu.A.; Yanchuk, I.B. (Functional Materials, 2004)
The mechanisms of structure formation of Ti-C system layers have been studied. The layers have been obtained at nonequilibrium process of transition of vapors with necessary component ratio into condensed state. Various levels of the condensation process nonequilibrium have been reached by exposure of the growth surface by electron streams with different intensities. Some regularities of transition of the metastable compound TiC2 into diamond phase have been determined by complex studies of physical properties of the condensates using methods of electron diffraction analysis, Raman scattering.